2011
DOI: 10.1007/s11604-010-0524-z
|View full text |Cite
|
Sign up to set email alerts
|

Single-slice epicardial fat area measurement: do we need to measure the total epicardial fat volume?

Abstract: The EFA is significantly correlated with the EFV. The EFA is a simple, quick method for representing the time-consuming EFV, which has been used as a predictive indicator of cardiovascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 18 publications
0
33
1
1
Order By: Relevance
“…Oyama et al . [17] described a method of estimating the total EFV by MSCT scan, using a single MSCT slice located at the level of the LMCA. Single slice epicardial fat area (ssEFA) measured at the level of the LMCA correlated well with total EFV in this study (r = 0.92; P < 0.0001) [17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oyama et al . [17] described a method of estimating the total EFV by MSCT scan, using a single MSCT slice located at the level of the LMCA. Single slice epicardial fat area (ssEFA) measured at the level of the LMCA correlated well with total EFV in this study (r = 0.92; P < 0.0001) [17].…”
Section: Methodsmentioning
confidence: 99%
“…[17] described a method of estimating the total EFV by MSCT scan, using a single MSCT slice located at the level of the LMCA. Single slice epicardial fat area (ssEFA) measured at the level of the LMCA correlated well with total EFV in this study (r = 0.92; P < 0.0001) [17]. We used a similar method as Oyama et al The EFV of two MSCT slices nearest the origin of the LMCA were measured on each patient (GE Advantage Workstation, “volume tool”).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used maximal thickness and area of both layers as indices of total amount and groove thickness as indices of varying fat distribution. EFA is a highly reproducible index of EF quantity and is significantly correlated with EF total volume, but simpler and less prone to under or overestimation when measured manually [26]. We found that the radiodensity of both layers was related to the amount of fat, but there were no significant associations with any other ultrasound fat indices, CV risk factors, or MS.…”
Section: Epicardial (Ef) and Pericardial Fat (Pf)mentioning
confidence: 61%
“…MDCT can provide more accurate measurements than other techniques because of its high temporal resolution [1], and MDCT measurements are reproducible [2,3]. It has also been shown that MDCT volumetric measurements are more reliable than echocardiographic thickness measurements [4].…”
Section: Introductionmentioning
confidence: 99%